A View on People's Hesitancy Perception towards Covid-19 Vaccination in Kupang City and Kupang Regency - Aleta Agustina Puling; Indra Yohanes Kiling; Shela Ch Pello (Journal of Health and Behavioral Science, 2022)
Abstract. The vaccination program is a policy initiative aimed at slowing the spread of the covid-19 virus by enhancing individual body immunity and forming group immunity. The government's efforts are not fully accepted by the public; there are doubts about the covid-19 vaccine, and doubts about the covid-19 vaccine are influenced by public perceptions; therefore, efforts to uncover the picture of perceptions that raise doubts about the covid-19 vaccine are required in order to develop targeted treatment. Methods The results of collecting data with twelve participants who had doubts about the COVID-19 vaccine revealed that understanding of the virus and the COVID-19 vaccine, emotional reactions to the vaccination process, vaccine side effects, and vaccine certificate policies are components that form doubts about the COVID-19 vaccine. The findings of this study also suggest that if an individual has strong confidence in social groups, limited comprehension of the covid-19 vaccine, fear of social reprimand, and fear of deviation, skepticism might cause vaccination delays and conforming behavior toward obtaining the covid-19 vaccine.